Upaya Guru Kelas dalam Mengatasi Kesulitan Belajar Matematika (Diskalkulia) pada Siswa Kelas V SDN Gunggung 1 - rafikatul arifa; Bella Helliyana Febria; Moh. Ainor Rofiqi (Jurnal Pengabdian Pendidikan, 2025)
Difficulties in learning mathematics are problems often experienced by elementary school students, especially in basic arithmetic operations that can have an impact on academic achievement and attitudes towards mathematics in the future. This study aims to examine teachers' efforts in overcoming difficulties in learning mathematics in grade V students, especially those with dyscalculia. The study used a qualitative approach with a case study method at SDN Gunggung 1, with grade V homeroom teachers as research subjects selected by purposive sampling. Data were collected through in-depth interviews and analyzed using qualitative descriptive analysis techniques. The results of the study showed that grade V students experienced difficulties in learning mathematics, especially in multiplication and division operations caused by low learning motivation, minimal parental supervision due to work, and dependence on technology that reduces the habit of memorizing basic concepts. Efforts made by teachers include strengthening memorization of multiplication, implementing heterogeneous group learning, and communicating with parents through home visits. This study concludes that success in overcoming difficulties in learning mathematics requires effective collaboration between teachers, schools, and parents to create optimal learning continuity. Kesulitan belajar matematika merupakan permasalahan yang sering dialami siswa sekolah dasar, khususnya dalam operasi hitung dasar yang dapat berdampak pada prestasi akademik dan sikap terhadap matematika di masa depan. Penelitian ini bertujuan untuk mengkaji upaya guru dalam mengatasi kesulitan belajar matematika pada siswa kelas V, khususnya yang mengalami diskalkulia. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus di SDN Gunggung 1, dengan guru wali kelas V sebagai subjek penelitian yang dipilih secara purposive sampling. Data dikumpulkan melalui wawancara mendalam dan dianalisis menggunakan teknik analisis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa siswa kelas V mengalami kesulitan belajar matematika terutama pada operasi perkalian dan pembagian yang disebabkan oleh rendahnya motivasi belajar, minimnya pengawasan orang tua akibat kesibukan kerja, dan ketergantungan pada teknologi yang mengurangi kebiasaan menghafal konsep dasar. Upaya yang dilakukan guru meliputi penguatan hafalan perkalian, penerapan pembelajaran kelompok heterogen, dan komunikasi dengan orang tua melalui kunjungan rumah. Penelitian ini menyimpulkan bahwa keberhasilan mengatasi kesulitan belajar matematika memerlukan kolaborasi efektif antara guru, sekolah, dan orang tua untuk menciptakan kontinuitas pembelajaran yang optimal.